Two novel entomopathogenic fungal species of Lecanicillium isolated from soil in China - Tongyi Liu; Wei Chen; Yanhong Tang; Fen Liu; Liyan Yao; Qiongbo Hu; Ke Zhang; Qunfang Weng (BMC Microbiology)
Abstract The genus Lecanicillium was established in 2001 based on the type species Lecanicillium lecani (former, Verticillium lecani), which is an important entomopathogenic fungus. To date, more than thirty species in the genus have been reported, but much more are waiting to discover. In this study, two novel species isolated from soil in east China were identified. They differ from known closely related species primarily in sporulation structure, conidia and colony morphological characteristics, and sequence variations in the LSU, SSU, ITS, and TEF gene regions of the ribosomal DNA. Multigene phylogenetic analysis has provided strong molecular evidence supporting the classification of the strains, AH13B2 and JX15A210 within the genus Lecanicillium. The new species are formally named as follows: L. anqingense sp. nov. and L. renii sp. nov., respectively. Bioassays conducted on the greater wax moth, Galleria mellonella and crucifer aphid, Lipaphis erysimi showed that both fungal strains exhibit virulence. When treating with 1 × 108 spores/mL, the two strains gave mortality of > 60% and > 80% to G. mellonella and L. erysimi, respectively. Moreover, the median lethal times (LT50) of L. renii JX15A210 and L. anqingense AH13B2 against G. mellonella and L. erysimi were recorded as 8.06 d and 4.18 d, and 10.63 d and 5.07 d, respectively. This research enhances the species diversity within the genus Lecanicillium and provides valuable genetic resources for the biological control of pests and the development of biocontrol agents.